Tingkat Pendapatan dan Kesejahteraan Petani Salak pada Kelompok Tani Dukuh Lestari di Desa Sibetan, Kecamatan Bebandem, Kabupaten Karangasem - DWIANI, DILLA; ARTINI, NI WAYAN PUTU; SUARDI, I DEWA PUTU OKA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2020)
Snake Fruit Farmers' Income and Welfare in Dukuh Lestari Farmer Groups in Sibetan Village, Bebandem District, Karangasem Regency  This study aimed to determine the level of income and welfare of salak farmers in Dukuh Lestari Farmer Groups using quantitative and qualitative analysis methods. The data collection was done through interview and literature study methods. The selection of the number of sample was determined by taking the entire population of Dukuh Lestari Farmers group totaled 39 people. The variables in this study were income, farm R/C Ratio value and welfare level with indicators used were income, expenditure and consumption patterns, health, education, employment, and housing. The results of this study were that the average income of the salak farming cash costs was Rp. 24,315,224.34 / ha / year with an R / C ratio of 5.08 and the income on the total costs of salak farming was Rp. 22,221,705.07 / ha / year with an R / C ratio of 3.76. The results for the welfare level of salak farmers was in the quite prosperous category with an achievement score of 55.63 percent. Based on the overall results of the study, it can be concluded that it is necessary to increase the income of salak farming for the welfare of Dukuh Lestari Farmer Groups, it can be suggested that they should increase farm income, provide facilities in the form of production facilities and other necessary agribusiness development facilities such as market information, increasing market access, capital, and the development of partnership with other business institutions.